Collaborative Pentahelix in Supporting Community-based Maggotization through the Climate Village Program in Bandung City - Julia, latrijuliasari02 (GoResearch - Research & Publishing House, 2025)
The problem of organic waste management in Bandung City, which accounts for 60% of the 1,600 tons of daily waste, requires innovative solutions through cross-sectoral collaboration. This study analyzes the implementation of the collaborative penthahelix model in a maggotization program using Black Soldier Fly (BSF) larvae in RW 14, Cipadung Village, Bandung City. Using qualitative methods including in-depth interviews, observations, and literature reviews, this study analyzes the dynamics of interaction among the five penthahelix factors: academia, business, community, government, and media. The results show that the maggot program successfully processed 80% of daily organic waste and benefited 65% of RW 14 residents. Academics played a role in education and technical assistance, the government provided regulations and facilities, the community actively optimized the integrated program, and the media played a role in publicity. However, the business sector has not yet optimized the economic value of maggot products. The study concludes that the collaborative pentahelix model in maggotization shows significant potential for sustainable organic waste management, but requires strengthening the role of the business sector to create sustainable community self-reliance.